2021
DOI: 10.1002/acn3.51311
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial morphology and MAVS‐IFN1 signaling pathway in muscles of anti‐MDA5 dermatomyositis

Abstract: Objective This study aimed to investigate mitochondrial changes and the mitochondrial antiviral‐signaling protein (MAVS)‐type I interferon (IFN1) signaling pathway in the muscles of anti‐melanoma differentiation gene 5(MDA5) dermatomyositis (DM) patients. Methods Eleven anti‐MDA5 DM and ten antibody‐negative DM patients were included. Muscle biopsies were performed in all patients. Muscle pathology and mitochondrial morphology in particular were compared between two groups. The expression of MDA5, MAVS, interf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 27 publications
(65 reference statements)
1
10
0
Order By: Relevance
“…Complement membrane attack complex deposition is rarely observed. Furthermore, IFN signature in skeletal muscles of patients with anti-MDA5 DM is up-regulated, compared with healthy subjects but lower than patients with anti-MDA5 negative DM ( 21 , 22 ). These observations are consistent with the mild muscle phenotype frequently associated with anti-MDA5 DM.…”
Section: Clinical Spectrum In Adults Of the Dermatomyositis With Anti-mda5 Antibodiesmentioning
confidence: 87%
See 3 more Smart Citations
“…Complement membrane attack complex deposition is rarely observed. Furthermore, IFN signature in skeletal muscles of patients with anti-MDA5 DM is up-regulated, compared with healthy subjects but lower than patients with anti-MDA5 negative DM ( 21 , 22 ). These observations are consistent with the mild muscle phenotype frequently associated with anti-MDA5 DM.…”
Section: Clinical Spectrum In Adults Of the Dermatomyositis With Anti-mda5 Antibodiesmentioning
confidence: 87%
“…When present, muscle damage mainly affects proximal muscles ( 2 , 12 ). Several histological features of muscle biopsies are shared by different forms of DM, and include perifascicular fiber atrophy, perivascular inflammation, infiltrates of T and B cells, diffuse class I major histocompatibility complex (MHC-I) expression and deposition of complement attack complex ( 21 , 22 ). In contrast, muscle biopsies of patients with anti-MDA5 DM are often normal or highlight only rare anomalies.…”
Section: Clinical Spectrum In Adults Of the Dermatomyositis With Anti-mda5 Antibodiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the IFN signature was up-regulated in groups of patients with MDA5 + DM and classic DM when compared with normal muscle, the up-regulation of ISGs was less significantly in MDA5 + DM patients than that in classic DM patients ( 41 ). A study from China investigated the mitochondrial changes and MAVS-type I IFN signaling pathways in the muscles of MDA5 + DM patients ( 42 ). These authors found that the IFN-I inducible proteins (MDA5, MAVS, IRF7, and ISG15) were overexpressed in the muscles of MDA5 + DM patients, suggesting that the MAVS-type I IFN pathway is broadly involved in the muscle pathology of MDA5 + DM.…”
Section: Footprints Of Ifn I System In Organs Involved In Mda5 + Dmmentioning
confidence: 99%